The Relationship Between Religiosity and Psychological Well-Being in the Elderly: Hubungan Antara Religiusitas dengan Kesejahteraan Psikologis pada Lanjut Usia - Elfahmi, Muhammad Alghozi Rizky Robby; Mariyati, Lely Ika (Indonesian Journal of Innovation Studies, 2023)
This study aims to determine the relationship between religiosity and psychological well-being in the elderly at Griya Wreda Jambangan Surabaya. This research is a type of quantitative research, using a saturated sampling method on the existing population, namely 152 elderly subjects at Griya Wreda Jambangan Surabaya. The data obtained were then processed using normality test, linearity test, classical assumption test and hypothesis testing. Through the results of the product moment correlation test on the data obtained the results are 0.999** or close to 1. It can be found that there is a positive relationship between one's religiosity and psychological well-being. Referring to the significance value where 0.000 <0.05, it means that Ha is accepted, namely there is a relationship between religiosity and the psychological well-being of the elderly, where the higher the level of religiosity of the elderly, the higher the psychological well-being they have. Based on the value of Adjusted R Square in the tests conducted by researchers, the results obtained 66.8% where religiosity dominantly affects a person's psychological well-being, influenced by other variables being studied by researchers.